An educational initiative aimed at increasing antimicrobial resistance awareness among school-going Jordanian youth - Qenab, Basmah; Aqel, Tahreer; Younis, Hanin; AbuShweimeh, Rahmeh; Al Zghoul, Anwaar; Sweedan, Zaina; Omran, Mohammad; Joshi, Mohan P.; Konduri, Niranjan (Frontiers in Public Health, 2024)
BackgroundThe World Health Organization (WHO) has recommended strategies and actions to enhance awareness and understanding of AMR. Gaps in AMR awareness remain in Jordan, particularly among the youth.AimTo describe our programmatic approach to AMR education across Jordanian governorates among school-aged children.MethodsOur approach depicts the development of comprehensive health messages, pilot and expansion phases in schools, and pre- and post-session knowledge assessments.Results2,700 students across 30 schools reached with AMR health messages. Gained knowledge was assessed in 932 students, revealing significant improvements in understanding the importance of consulting a doctor before taking antibiotics, the relationship between nutrition and immunity, the dangers of sharing medicines, and proper handwashing techniques. The average expenditure was approximately 8.55 per student.ConclusionThe intervention underscores the critical role of targeted educational initiatives in improving AMR awareness among youth, emphasizing the need for sustained and scalable approaches to combat AMR effectively.